Participatory assessment of critical thresholds for resilient and sustainable European farming systems. (December 2021) - Paas, Wim; Accatino, Francesco; Bijttebier, Jo; Black, Jasmine E.; Gavrilescu, Camelia; Krupin, Vitaliy; Manevska-Tasevska, Gordana; Ollendorf, Franziska; Peneva, Mariya; San Martin, Carolina; Zinnanti, Cinzia; Appel, Franziska; et al.
Abstract: Farming systems in Europe are experiencing multiple stresses and shocks that may push systems beyond critical thresholds after which system change is expected to occur. These critical thresholds may lie in the economic, environmental, social and institutional domain. In this paper we take a participatory approach with involvement of farming system stakeholders to assess the presence of critical thresholds in 11 European farming systems, and the potential consequence of surpassing those with regard to system sustainability and resilience. First, critical thresholds of the main challenges, key system variables and their interactions in the studied farming systems were assessed. Second, participants assessed the potential developments of the key system variables in case critical thresholds for main system challenges would be exceeded. All studied systems were perceived to be close, at or beyond at least one identified critical threshold. Stakeholders were particularly worried about economic viability and food production levels. Moreover, critical thresholds were perceived to interact across system levels (field, farm, farming system) and domains (social, economic, environmental), with low economic viability leading to lower attractiveness of the farming system, and in some farming systems making it hard to maintain natural resources and biodiversity. Overall, a decline in performance of all key system variables was expected by workshop participants in case critical thresholds would be exceeded. For instance, a decline in the attractiveness of the area and a lower maintenance of natural resources and biodiversity. Our research shows that concern for exceeding critical thresholds is justified and that thresholds need to be studied while considering system variables at field, farm and farming system level across the social, economic and environmental domains. For instance, economic variables at farm level (e.g. income) seem important to detect whether a system is approaching critical thresholds of social variables at farming system level (e.g. attractiveness of the area), while in multiple case studies there are also indications that approaching thresholds of social variables (e.g. labor availability) are indicative for approaching economic thresholds (e.g. farm income). Based on our results we also reflect on the importance of system resources for stimulating sustainability and resilience of farming systems. We therefore stress the need to include variables that reflect system resources such as knowledge levels, attractiveness of rural areas and general well-being of rural residents when monitoring and evaluating the sustainability and resilience of EU farming systems. Highlights: Concern on exceeding critical thresholds is justified as studied farming systems are perceived to be close to such thresholds. Challenges in the environmental domain were least often perceived to have reached critical thresholds. Economic viability at farm level is a central, interacting critical threshold observed in all farming systems. The economic, environmental as well as social domain are important for the sustainability and resilience of farming systems.